DEVELOPMENT OF NATIONAL CLIMATE DATABASE SYSTEM FOR SUPPORTING AGRICULTURE RESEARCH - RUNTUNUWU, ELEONORA (Jurnal Sumberdaya Lahan, 2010)
One of the most significant challenges for improving the agroclimate research is availability of integrated climate data. This paper reviewed several climate database systems development of national and international levels; such as those produced by Indonesian Meteorological ClimatologicalÂ  and Geophysical Agency (BMKG), World Meteorological Organization (WMO), and New Zealand climatic database systems. Indonesian Agency for Agricultural Research and Development (IAARD) through Indonesian Agroclimate and Hydrology Research Institute (IAHRI) hasÂ  developed a national climate database system (CDS), called as IAHRI CDS, as a basic part of agroclimatic researches. The system was integrated the numeric climate data and thematic spatial maps by applying Geographic Information System (GIS) and programming technologies. The data mainly comes from automated and manual climate stations of Ministry of Agriculture, BMKG and Irrigation service of each province. The development of IAHRI CDS is expected as a great resource for many potential applications on agriculture research in Indonesia. Keywords : Aagriculture, climate, database system, Indonesia